Human vs Nature - Akter, Md.Shaon; Yunus, Khwaja; Hussain, Md.Asgor; Sanaullah, kushtia Md. (IJRDO - Journal of Social Science and Humanities Research, 2017)
Every Single writer has used nature for writing poem, short story, drama, novel, fiction and nonfiction. I have read three texts in many times such as The Old Man and the Sea, Riders to the Sea and Moby Dick in which all three writers show the power of Nature. Here John Millington Synge and Herman Melville surrender to Nature but Earnest Hemingway does not surrender to Nature.This thinking will be proved through discussion of three texts in below.